SOME ASPECTS OF MINING AND INFORMAL WORK IN PERU AND IN THE CONTEXT OF THE COVID-19 - Solange Julca Gonza, Flor de Maria [UNESP]; Barbosa Borges, Gerson Antonio [UNESP]; Julca Gonza, Editha Lisbet [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2020)
In this text we present some aspects of the work in the peruvian extractive sector in the context of the pandemic caused by covid-19. With a view to show the consequences of the developmental imaginary based on an economy of mining exploitation and its impact on the lives of (informal) workers, and on the vulnerability of workers in the sector. Through the bibliographic and documents review we intend to contribute to the debate on the complex process faced by workers in the current context, a situation that reveals the crisis of the extractive economic model.
Keywords: Informal work; Mining; Covid-19